Calcium and Calmodulin Are Involved in Nitric Oxide-Induced Adventitious Rooting of Cucumber under Simulated Osmotic Stress - Niu, Lijuan; Yu, Jian; Liao, Weibiao; Yu, Jihua; Zhang, Meiling; Dawuda, Mohammed M. (Frontiers in Plant Science, 2017)
Osmotic stress is a major form of abiotic stress that adversely affects growth and development of plants and subsequently reduces yield and quality of crops. In this study, the effect of nitric oxide (NO) and calcium (Ca2+) on the process of adventitious rooting in cucumber (Cucumis sativus L.) under simulated osmotic stress was investigated. The results revealed that the effect of exogenous NO and Ca2+ in promoting the development of adventitious roots in cucumber seedlings under simulated osmotic stress was dose-dependent, with a maximal biological response at 10 μM NO donor nitroprusside (SNP) or 200 μM Ca2+. The application of Ca2+ chelators or channel inhibitors and calmodulin (CaM) antagonists significantly reversed NO-induced adventitious rooting, implying that endogenous Ca2+/CaM might be involved in NO-induced adventitious rooting under osmotic stress. Moreover, intracellular Ca amount was also increased by NO in cucumber hypocotyls during the development of adventitious roots under osmotic stress. This increase of endogenous Ca2+ was inhibited by NO specific scavenger 2-(4-carboxyphenyl) -4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt (cPTIO), nitrate reductase inhibitors tungstate (Na2WO4) and sodium azide (NaN3). This gives an indication that Ca2+ might be a downstream signaling molecule in the adventitious root development by NO under osmotic condition. The results also show that NO or Ca2+ play a positive role in improving plant water status and photosynthetic system by increasing chlorophyll content and photochemical activity in leaves. Furthermore, NO and Ca2+ treatment might alleviate the negative effects of osmotic stress by decreasing membrane damage and reactive oxygen species (ROS) production by enhancing the activities of superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX). Therefore, Ca2+/CaM may act as a downstream signaling molecule in NO-induced development of adventitious root under simulated osmotic stress through improving the photosynthetic performance of leaves and activating antioxidative system in plants.